Mediasi Elektronik Sebagai Perwujudan Asas Peradilan Cepat, Sederhana, dan Biaya Ringan - Jasmaniar, Jasmaniar; Khalid, Hasbuddin (UNES Law Review, 2023)
This paper analyzes the problem of electronic mediation as a manifestation of the principles of fast, simple and low-cost justice. The main problem in researching the essence of the principle of fast, simple, low-cost justice through electronic trials and the beneficial value of mediation carried out electronically. This research is normative juridical research with primary and secondary legal materials analyzed descriptively qualitatively. The essence of the principle of fast, simple and low-cost justice is legal certainty for the parties involved in the case without prejudice to the value of justice and benefit, while the value of the benefit of electronic mediation is the ease in resolving disputes, the relatively short time compared to settlement by judge's decision, and the costs involved. affordable.